Los dominicos en el contexto de la primera evangelización de México: (1526 - 1550) - Fernández Rodríguez, Pedro (Monumenta histórica iberoamericana de la Orden de Predicadores, 1994)
"Chronological history of the Dominican Order. Re-examines the issue of the anti-indigenism of Fr. Domingo de Betanzos seeking a revindication of this figure"--Handbook of Latin American Studies, v. 58